Correlation between socio-demographic, nutritional and clinical markers and poor sleep quality among hemodialysis patients in Sibu, Sarawak, Malaysia - Ho, Lina Ling Ling (2018)
Chronic kidney disease is a global health problem with increasing prevalence of patients receiving renal replacement therapies such as peritoneal dialysis, hemodialysis, and transplantation. Poor sleep quality affected 51% to 91% of hemodialysis patients which was relatively more prevalent than general population (33% to 42%). Poor sleep quality was often associated with adverse clinical outcomes such as higher morbidities and affected immunity and diminished quality of life among general population as well as hemodialysis patients, but limited evidence was available on sleep quality and its correlation among hemodialysis patients in local context. This cross-sectional study aimed to determine whether socio-demographic, nutritional and clinical markers could be associated with poor sleep quality among hemodialysis patients in Sibu, Sarawak, Malaysia. Sleep quality of subjects on both dialysis and non-dialysis days was assessed using Pittsburgh Sleep Quality Index (PSQI). A pre-tested structured questionnaire was used to obtain socio-demographic background while relevant biochemical parameters and clinical parameters were retrieved from medical and dialysis records. Nutritional status of the subjects was assessed using established Dialysis Malnutrition Score (DMS) while anthropometric measurements and hand grip strength (HGS) test were assessed using standardized protocols. Dietary intake was ascertained by three 24-hour dietary recalls (one dialysis day, one non-dialysis day, and one weekend). SPSS version 22.0 was used in statistical analysis of correlation and contribution of variables towards sleep quality. Multistage sampling was applied where cluster sampling was used in choosing study location and proportionate stratified random sampling was used in selecting subjects. A total of 184 subjects was recruited with mean age of 54.3 ± 12.6 years and comprised of 61% of male. Mean DMS, body mass index, mid-arm muscle circumference, and HGS were 11.3 ± 2.3, 24.2 ± 4.6 kg/m2, 26.1 ± 3.9 cm, and 20.9 ± 9.0 kg, respectively. Based on Kidney Disease Outcomes Quality Initiative (K/DOQI) guidelines, approximately 40% of the subjects were hypoalbuminemic, one-third was hypocholesterolemic and hyperphosphatemic, and one-quarter was hyperkalemic. More than three quarters of the subjects had inadequate dietary energy and protein intake. Poor sleepers had significantly higher dietary protein, potassium, and sodium intake (p < 0.05). Subjects had a mean dialysis vintage of 56.9 ± 51.1 months, dialysis adequacy (Kt/V) of 1.5 ± 0.3, and interdialytic weight gain (IDWG) of 3.4 ± 1.2%, with 30% of them had excessive IDWG. Slightly more than half of the subjects were poor sleepers when measured objectively. However, there was only approximately 15% self-rated themselves had poor sleep. Approximately two-third of the subjects had sleep latency more than 15 minutes and sleep duration less than seven hours, respectively. There were significant longer sleep latency and shorter sleep duration among the subjects on non-dialysis day. Six in ten subjects had difficulty with sleep efficiency. Sleep disturbances were evident while use of sleep medication was spared. Daytime dysfunction was seen in 30% of the subjects. Men (r = 0.160, p = 0.030), higher DMS (r = 0.152, p = 0.039), smaller triceps skinfold (r = -0.147, p = 0.047), hyperkalemia (r = 0.161, p = 0.029), higher dietary protein (r = 0.157, p = 0.035) and sodium (r = 0.162, p = 0.028) intakes correlated significantly with higher global PSQI score, hence poorer sleep quality. None of the clinical variables (IDWG, dialysis vintage, and Kt/V) was significantly correlated with sleep quality. Overall, the multiple regression model explained 14.5% of variance in global PSQI score with calcium intake from supplementation contributed greatest (4.0%), followed by dietary sodium intake (3.1%), serum potassium (2.9%), male sex (2.6%), and the least by HGS (2.0%). Hence, higher calcium intake from supplementation, lower dietary sodium intake, lower serum potassium, and greater HGS were the modifiable risk factors that contributed to better sleep quality among the hemodialysis patients. In conclusion, this study showed a high prevalence of poor sleep quality and variables such as men, widowhood, HGS, malnutrition, lower triceps skinfold, hyperkalemia, higher dietary protein and sodium intake, and lower calcium intake from supplementation contributed significantly to poor sleep quality. The results emphasized the needs of routine nutritional assessment and appropriate intervention in improving the sleep quality among hemodialysis patients.